Capturing The Bride Culture In Sumba, East Nusa Tenggara: A Victimological Analysis - Nurani, Siti Syahida; Angkasa, Angkasa; Budiono, Arief; Nurdin, Nurdin; Dewi, Dyah Adriantini Sintha (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The Sumba people has a culture called ‘capturing the bride’ (kawin tangkap), where a man captures the woman he will marry. But its practice has deviated and it became full of intimidation. This paper aims to analyze the ‘capturing the bride’ practice of Sumba people from the victimological perspective. This was descriptive qualitative research. Results show that the current form of ‘capturing the bride’ is a form of violence against women. The violence experienced by ‘capturing the bride’ victims is motivated by a created opportunity and a man’s idealized need to marry a woman. From the victimological perspective, based on Mendelshon’s theory on the degree of victims’ fault, the above victims are completely innocent victims. Based on Schafer’s concept on victim responsibility, they are categorized as biologically and socially weak victims. Then, if related to Fattah’s theory on victim involvement, they are categorized as non-participating victims.